Assessment of nickel cermets and La0.8Sr0.2Sc0.2Mn0.8O3 as solid-oxide fuel cell anodes operating on carbon monoxide fuel - Su, C.; Wu, Y.; Wang, W.; Zheng, Y.; Ran, R.; Shao, Zongping (Elsevier SA, 2010)
Ni-SDC, Ni-ScSZ, and La0.8Sr0.2Sc0.2Mn0.8O3 (LSSM) anodes are investigated for SOFCs operating on CO. O2-TPO and SEM results demonstrate LSSM is greatly superior to nickel cermet anodes in suppressing carbon deposition. H2-TPR suggests there is strong chemical interaction between NiO and ScSZ, which helps to suppress the carbon deposition. Raman spectroscopy of the carbon-deposited nickel cermet anodes demonstrates the graphitization degree of carbon is enhanced with increasing temperature. The cell performance is much lower operating on CO as compared to H2, and the reduction is the largest for the cell with Ni-SDC anode. Furthermore, steady performance degradation is observed for all three cells operating on pure CO which is irreversible for the cell with Ni-SDC anode while largely reversible for the cell with Ni-ScSZ anode. The degradation for the cell with an LSSM anode is found to be due to the phase instability of LSSM in pure CO atmosphere. By applying a mixture of CO and CO2 as the fuel or under polarization, the phase of LSSM is stabilized; as a result, the cell is stably operated on CO under current polarization. This suggests that LSSM and Ni-ScSZ anodes are greatly superior to the Ni-SDC anode for operation on CO. © 2009 Elsevier B.V. All rights reserved.